The events of the Jawes in Constantine In 1934, and their effects on the Algerian national movement through An-Najah newspaper. - LARBI Ismail (Pensées Genre, Penser Autrement)
The written press is considered an important source for historical writing, given that it contains details of events, their effects, and their repercussions. Perhaps An-Najah newspaper is one of the many examples of newspapers and magazines that have provided rich scholarly material for those interested in historical studies, researchers, and historians. This is because it was able to address various issues related to Algeria. Its journalists and columns covered political, religious, cultural, social, and economic topics, in addition to many aspects of French colonial policy in Algeria. In this study, I attempt to shed light on one of France's practices within the framework of its colonial policy, aiming to consolidate its presence in Algeria and achieve its colonial project. This concerns the events that erupted in Constantine in August 1934, in which the colonial administration played a significant role in fueling them and attempting to exploit them to its advantage. In addition, I examine the effects and repercussions of these events, and attempt to examine An-Najah newspaper's perspective on these events.